Outcomes of persistent and long-standing persistent atrial fibrillation ablation: a systematic review and meta-analysis. Issue Volume 20:Issue FI 3(2018) (15th December 2017) - Clarnette, Jock A; Brooks, Anthony G; Mahajan, Rajiv; Elliott, Adrian D; Twomey, Darragh J; Pathak, Rajeev K; Kumar, Sharath; Munawar, Dian A; Young, Glenn D; Kalman, Jonathan M; Lau, Dennis H; Sanders, Prashanthan
Abstract: Aims: Several techniques have been utilized for the ablation of persistent (P) and long-standing persistent (LsP) atrial fibrillation (AF); however, the best approach of substrate ablation remains poorly defined. This study aims to examine the impact of ablation approach on outcomes associated with P or LsP AF ablation by conducting a meta-analysis and regression on contemporary literature. Methods and results: A systematic literature review was conducted up to 29 July 2015 for scientific literature reporting on outcomes associated with P or LsP AF ablation. One hundred and thirteen studies reported outcomes in a total of 18 657 patients undergoing various ablation approaches for the treatment of P–LsP AF between 2001 and 2015. The point efficacy estimate of a single-AF ablation procedure without the use of anti-arrhythmic drugs was 43% (95% CI; 39–47%). Multiple procedures and/or the use of anti-arrhythmic drugs increase success to 69% (95% CI; 66–71%). Meta-regression revealed that ablation technique ( P  < 0.001) and left atrial size ( P  = 0.02) were predictive of single procedure, drug-free success. The addition of extra-pulmonary substrate approaches was associated with declining efficacy when compared to a pulmonary vein ablation alone. Conclusion: The efficacy of a single-AF ablation procedure for P or LsP AF is 43%; however, can be increased to 69% with the use of multiple procedures and/or anti-arrhythmic drugs. Current literature supports the finding that pulmonary vein antrum ablation/isolation is at least equivalently efficacious to other contemporary P–LsP ablation strategies.